[Cranfield DrivAer] CAD_Pack_2 Rear-end (Standard DrivAer) - Francisco Soares, Renan; Garry, Kevin; Holt, Jenny (Cranfield University, 2018)
Rear-end CAD Pack (35% scaled-version), including:1. DrivAer - Rear-end Fastback (F):Rear-end surface equivalent to a generic Fastback car model.2. DrivAer - Rear-end Notchback (N):Rear-end surface equivalent to a generic Notchback car model.3. DrivAer - Rear-end Estateback (E):Rear-end surface equivalent to a generic Estateback car model.CAD files available in IGS, STEP, STL, and Parasolid formats. All geometries are provided in [mm].Notation:(F) = Fastback(N) = Notchback(E) = EstatebackReference:1. DrivAer Model : “Geometry”. Institute of Aerodynamics and Fluid Mechanics. Technical University of Munich. http://www.aer.mw.tum.de/en/research-groups/automotive/ drivaer/geometry/.-CAD adapted and uploaded by:Renan F Soares - PhD in AerospaceApplied Aerodynamics GroupCranfield University, United Kingdom
Keywords: CAD'; 'DrivAer'; 'Automotive'; 'Aerodynamics'; 'Aerodynamics (excl. Hypersonic Aerodynamics)'; 'Automotive Engineering not elsewhere classified'